Age-related muscle function identification using emg amplitude analysis - Muhammad Saufi, Sanusi (2016)
The relationship between electromyography (EMG) and age group is to identify and analysis the electrical activity/signal on upper-limb muscle. Nine participants/subjects with their arm fixed at 90º angle and perform isometric contraction using the dynamometer. The EMG is one kind of biological signal that can be recorded by using signal sensors. A raw EMG signal is obtained from the experiment and then will be filtered to get accurate results. The Root-Mean-Square (RMS) and Mean-Absolute-Value (MAV) is then obtained by using the calculations from the raw data. The results shows the EMG activity for younger age group is more significant (higher activity) compare to the adult and older age group.